Mechanical characteristics of developed brick from drinking water sludge under different firing temperatures and rice husk ash contents - Zulfahmi Ali Rahman,; Hafis Nazarah,; Wan Mohd Razi Idris,; Tukimat Lihan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
There is a considerable interest in making alternative bricks using wastes. Firing temperature has been significantly improved the mechanical qualities of bricks. The aim of this study was to investigate into the impact of firing temperature and rice husk ash content on the mechanical properties of drinking water sludge bricks (DWS). Two types of bricks were produced; bricks made of 100% DWS (DWS100) and bricks with 80% DWS and 20% RHA (DWS80). These samples were subjected to different thermal variations of 300 °C and 700 °C for three hours. The unfired brick samples were also prepared for reference. The volume changes of the DWS100 bricks increased as the firing temperature climbed up to 500 °C, before dropped at 700 °C. A similar behaviour was also exhibited by DWS80 bricks, however it shrunk at earlier temperature of 500 °C. At 500 °C and 700 °C, the density of bricks decreased dramatically, with DWS80 bricks consistently being lesser than DWS100 bricks. The water absorption of DWS80 brick began to decrease at 500 °C, a lower temperature than that of DWS100, as the firing temperature climbed. RHA-added bricks (DWS80) were anticipated to absorb more water than DWS100 bricks, but this did not occur. This presumably induced by the constriction of clay mineral structure rather than organic matter removal at high temperature per se. The compressive strength increased with the increase in temperature. It can be inferred that RHA can decrease the compressive strength of RHA-added bricks, despite the fact that a higher fire temperature significantly increased their strength.